Artistic Research: A Cuckoo’s Egg in Other Bird’s Nest or an Epistemologically Justified Strategy of Research? - Gedutis, Aldis; Michelkevičius, Vytautas (Problemos, 2021)
In the broader context of other types of research, the authors of this article seek to analyse the epistemological status of artistic research. Because of its transdisciplinary character, artistic research is interpreted ambiguously: on the one hand, it might be treated as an unjustified and illicit intervention into the scientific field, on the other hand, despite its peculiarities artistic research still might be capable of creating knowledge commensurable with the knowledge produced in other (scientific) disciplines. The major question the article seeks to answer is the following: is it possible to justify artistic research applying ready-made arguments in the philosophy of science?
Keywords: artistic research; epistemology; knowledge; art; transdisciplinarity